Godność osoby w ponowoczesności. Perspektywa personalizmu - Rusiniak, Marcin (Humaniora. Czasopismo Internetowe, 2025)
In the postmodern reality, clear tendencies are revealed towards depersonalization and reification of the human being, which do not favor respecting his personal dignity. Meanwhile, the protection of this dignity, excluding all exclusions, is one of the fundamental conditions for the happy life of individual people and communities. Only with the granting of the status of a personal being to all people without exception, there is a chance to create space for shaping a fraternal civilization of people aware of their status, possibilities and aspirations, capable of dialogue. Only in the perspective of personalism, preferring integral anthropology, universal axiology and respecting the transcendence of man, can a society of people united by something more than consumerism be built.